2022
DOI: 10.54319/jjbs/150515
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol Production from Biologically Pretreated Prosopis africana Pods using Pichia kudriavzevii SY4

Abstract: High costs and ethical issues have prompted research into novel non-food feedstocks for the fermentation-based manufacture of sustainable fuels. In this study, Prosopis africana pods (PAP), an underutilized substrate, was examined for its ability to produce bioethanol. The biomass was pretreated with four mushrooms to delignify it and enhance hydrolysis. A scanning electron microscopy (SEM) was performed on raw and pretreated PAP. The optimum hydrolysis conditions for the pretreated biomass were then determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…For instance, Prosogerin A and B in Prosopis essential oil work alongside the cell membrane to create their antibacterial effects. The linking of an ion through the cell membrane results from this contract, which alters the shape of the membrane structure (Adekiya et al, 2019;El-Imam et al, 2022). (Nwokocha & Williams, 2016) observed that essential oil might modify the fatty acid composition of the flesh of broiler chickens and relieve the growth depression caused by a challenge with Clostridium perfringens, by (Falade & Akeem, 2020a;Yanda et al, 2022) findings.…”
Section: Research Papermentioning
confidence: 99%
“…For instance, Prosogerin A and B in Prosopis essential oil work alongside the cell membrane to create their antibacterial effects. The linking of an ion through the cell membrane results from this contract, which alters the shape of the membrane structure (Adekiya et al, 2019;El-Imam et al, 2022). (Nwokocha & Williams, 2016) observed that essential oil might modify the fatty acid composition of the flesh of broiler chickens and relieve the growth depression caused by a challenge with Clostridium perfringens, by (Falade & Akeem, 2020a;Yanda et al, 2022) findings.…”
Section: Research Papermentioning
confidence: 99%